A novel π bridging method to graft graphene oxide onto carbon fiber for interfacial enhancement of epoxy composites. (5th January 2021) - Yan, Fei; Liu, Liu; Li, Kaixuan; Jin, Lin; Zhang, Mengjie; Liu, Yu; Xiao, Linghan; Ao, Yuhui
Abstract: Based on the inherent crystallite structure of carbon fiber, a novel and facile method was presented to balance the tedious steps and effectiveness of graphene oxide/carbon fiber (GO/CF) hierarchical reinforcement, by establishing π bridging of GO and CF under the assistance of pyrene-containing compounds, which was performed without chemical treatment of CF and GO. The surface chemical elements, functional groups, wettability, morphologies and surface structures of obtained reinforcements were characterized through XPS, FT-IR, dynamic contact angle, SEM and Raman spectroscopy, respectively. This method could implement at room temperature without causing damage to CF as indicated by filament tensile strength test. The resulted composites with a bridging agent of 72 mmol/L have the highest interlaminar shear strength, transverse fiber bundle strength and interfacial shear strength which increased by 49.3%, 117.1% and 59.1%, respectively, compared to pristine CF composites. Graphical abstract: Image 1 Highlights: A novel and facile strategy of π bridging was used to construct GO/CF structure. This method did not depend on the limited activated carbon atoms at the edge of CF. This method was performed at room temperature and would not disrupt GO or CF. This method affords a valuable guidance for preparing hierarchical reinforcement.